The Effect of The Value Clarification Technology Model on Elementary School Students' Learning Motivation in Social Studies Learning - Faridillah Fahmi Nurfurqon; Duhita Savira Wardani; Medita Ayu Wulandari (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is based on the finding that every student has abilities and life values that they are not aware of regarding value education. This study aims to analyze learning planning in an effort to increase students' motivation and learning outcomes in social studies learning with the Value Clarification Technology method. The research design uses a quasi-experimental research model. The data collected is in the form of quantitative data through formative tests, analysis of observation sheets, and document analysis. The number of research subjects consisted of 60 students divided into two classes, namely the experimental class and the control class. This research was conducted in a public school located in the Ciwidey District, Bandung Regency. The results showed that the application of the VCT model could increase students' motivation and learning outcomes in social studies learning. This is because the Value Clarification Technology model of the Value Analysis Type can be focused on things that are considered important by the teacher so that these important things can be observed in their entirety. The conclusion in this study is that learning using the Value Clarification Technique model of Value Analysis in Social Studies learning can increase students' motivation and learning outcomes.